PENGARUH MEDIA PEMBELAJARAN DAN GAYA KOGNITIF TERHADAP HASIL BELAJAR SEJARAH - Tanjung, Samsidar (History Department, Semarang State University and Historian Society of Indonesia, 2015)
This study aims to investigate the effect of multi-channel teaching media and cognitive styles toward the history learning achievement. This quantitative, experimental study employs a 2X2 factorial design. It involves two independent variables, i.e. multi-channel teaching media (X1) and cognitive styles (X2), and learning achievement (Y) as the dependent variable. Population of the study is all students of the History Education Department who are taking the History of Indonesia 3. Samples are selected from this group using random sampling and are collected by conducting Learning Achievement and Cognitive Style tests. Findings signify that: (1) Teaching activities which utilize teaching media by utility (making use of the environment) bring greater learning achievement compared to those that utilize teaching media by design. (2) There are differences between the learning achievements of students. Those with field-independent cognitive style show better achievement than students who are field-dependent. (3) Findings show that students of the Indonesian History 3 course who were taught using teaching media by utility obtain better learning achievement than those who were taught using teaching media by design. Making use of the media available in the immediate learning environment will make it easier for students to manipulate information that they receive with their respective cognitive structure.Â Penelitian ini bertujuan untuk mengetahui pengaruh media dan gaya kognitif terhadap hasil belajar sejarah. Penelitian menggunakan eksperimen ini menggunakan desain faktorial 2X2. Ini melibatkan dua variabel independen, yaitu media pembelajaran (X1) dan gaya kognitif (X2), dan prestasi belajar (Y) sebagai variabel dependen. Populasi penelitian ini adalah seluruh mahasiswa Jurusan Pendidikan Sejarah yang mengambil Sejarah Indonesia 3. Sampel dipilih menggunakan random sampling dan dikumpulkan dengan melakukan hasil Belajar dan tes Gaya kognitif. Temuan menandakan bahwa: (1) kegiatan Pengajaran yang memanfaatkan media pembelajaran by utility (memanfaatkan lingkungan) membawa hasil belajar yang lebih besar dibandingkan dengan mereka yang memanfaatkan media pembelajaran by design. (2) Ada perbedaan antara prestasi belajar siswa. Mereka dengan gaya kognitif menunjukkan prestasi lebih baik. (3) Temuan menunjukkan bahwa siswa dari kuliah Sejarah Indonesia 3 yang diajarkan menggunakan media pembelajaran by utility memperoleh prestasi belajar yang lebih baik daripada mereka yang diajarkan menggunakan media yang mengajar dengan by design. Memanfaatkan media yang tersedia di lingkungan belajar langsung akan memudahkan siswa untuk memanipulasi informasi yang mereka terima dengan struktur kognitif mereka masing-masing.Â